2010
DOI: 10.1007/s10103-010-0770-4
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser versus traditional scalpel. A preliminary histological analysis of specimens from the human oral mucosa

Abstract: Hyperplastic fibro-epithelial lesions are the most common tumor-like swellings in the mouth. The neodymium yttrium aluminium garnet (Nd:YAG) laser appears to be useful for the surgical treatment of these lesions. Some controversies of laser surgery concern the accuracy of pathological diagnosis as well as the control of thermal damage on the target tissue. The aim of this study was to establish if the thermal changes induced by the Nd:YAG laser may affect the histopathological diagnosis and the evaluation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 11 publications
2
59
3
2
Order By: Relevance
“…This corelates with the results of the other researchers investigating laser systems effects on the soft tissue in the oral cavity [8,9]. The advantage of the Er:YAG laser is a weeker penetration of the laser energy into the tissue (0.05 mm) and a presence of additional water cooling.…”
Section: Discussionsupporting
confidence: 84%
“…This corelates with the results of the other researchers investigating laser systems effects on the soft tissue in the oral cavity [8,9]. The advantage of the Er:YAG laser is a weeker penetration of the laser energy into the tissue (0.05 mm) and a presence of additional water cooling.…”
Section: Discussionsupporting
confidence: 84%
“…The 34 Histopathological specimens showed better incision quality and less tissue injuries with higher frequency and lower input power. 35 However, diode lasers also showed to be advantageous in excision of soft tissue. 36 Aras et al reported the comparison between diode laser and Er:YAG.…”
Section: Discussionmentioning
confidence: 99%
“…Laser assisted surgeries are easy to perform with less discomfort, minimal or no bleeding due to sealing of capillaries by protein denaturation and stimulation of clotting factor VII production, shorten healing time with reduced post operative bleeding and edema. 13 Histologically, laser wounds have been found to contain significantly lower number of myofibroblasts, thereby resulting in less wound contracture and scarring, and ultimately improved healing. Laser itself are antimicrobial and remove endotoxins from root surface.…”
Section: Discussionmentioning
confidence: 99%